Improving Letter Writing Ability Through Demonstration Methods Assisted by Wipe Clean Worksheet Media in Group B Children RAM NU East Rowokembu - Saadah Saadah (Journal of Teaching and Education, 2024)
In writing learning process at RAM NU East Rowokembu, there are difficulties because students often need to remember the shape of the letters of the alphabet, so writing the letters is unclear. This condition allowed the writer to conduct classroom action research in two cycles. This research aims to improve the ability to write letters using a demonstration method assisted by wipe-clean worksheet media for children in group B RAM NU East Rowokembu. The research methods used are quantitative and qualitative. The subjects of this research were ten children in class B1 RAM NU East Rowokembu. Observation, interviews and documentation were used as data collection techniques. The data acquisition tool uses an observation sheet. Data analysis uses qualitative and quantitative descriptive. It is said that the capacity to write letters is successful if the percentage reaches 75 -100% with the criteria of developing according to expectations (BSH). The research results showed that the ability to write letters in the pre-action stage reached an average percentage value of 10%. Then improvements were made in cycle I, which increased slightly with an average percentage of 30%. After the first cycle of intervention succeeded in influencing the ability to write letters, the level of success had yet to be achieved, so the next cycle needed to be carried out. The results of cycle II showed that the ability to write letters reached the final level of 80% according to the BSH criteria. So, letter writing skills increase in class B1 RAM NU East Rowokembu